Manhaj al-Takamul al-Teknologiya wa Atsaruhu fi Baramij I’dad Mu’allim al-Lughah al-‘Arabiyyah fi Nigeria - Garba, Ahmad (Al-Wazan: Journal of Arabic Education, 2024)
The process of educating Arabic language teachers in the modern era is in great need of digital skills and strategies, and these skills have become diverse, so educational institutions must keep up with these changes, from the rapid changes that are taking place in today's world, which have become part of the reality we live in. This article aims to highlight the importance of using digital applications in training Arabic language teachers, and its impact on the educational process to improve teachers' performance in completing their educational tasks and increasing their level of competence and ability in building the personality of students. This study uses a Qualitative approach with a Literature Review whose data sources come from related books and articles. The results show that Developing teachers' digital skills during training is one of the modern areas that is being discussed intensively in teacher professional development, thanks to the great developments in educational technology and the interest in improving electronic learning and teaching patterns. Although there are differences in defining the digital skills needed by teachers, they revolve around how to use and benefit from technology and its applications in the teaching profession, and this is evolving day by day, which confirms that developing digital skills must be a continuous process. It is also clear to the researcher that the idea of ​​using modern methods and skills in teaching Arabic is not new, but rather an old idea that developed when educators and linguists saw the need for it. This is one of the basic means of teaching Arabic in conditions suitable for every learner, and is an important step that helps in spreading Arabic in various parts of the world, as it makes it easier for those who are interested and interested in Arabic regarding the Islamic religion to learn it